2013
DOI: 10.1080/01690965.2013.837495
|View full text |Cite
|
Sign up to set email alerts
|

The ageing neighbourhood: phonological density in naming

Abstract: Aging affects the ability to retrieve words for production, despite maintainence of lexical knowledge. In this study, we investigate the influence of lexical variables on picture naming accuracy and latency in adults ranging in age from 22 to 86 years. In particular, we explored the influence of phonological neighborhood density, which has been shown to exert competitive effects on word recognition, but to facilitate word production, a finding with implications for models of the lexicon. Naming responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 69 publications
2
29
2
Order By: Relevance
“…Consistent with this idea, we know of no study on healthy college-aged English-speaking adults that have found inhibitory effects for PND on speech onset latencies. All previous studies on this population have either found facilitatory effects (current study, Vitevitch, 2002; Vitevitch & Sommers, 2003) or null effects (Gordon & Kurczek, 2014; Munson, 2007; Newman & Bernsetin Ratner, 2007; Vitevitch, Armbrüster, & Chu, 2004). In contrast, the studies conducted by Sadat et al (2014)—including reanalyses of additional studies on Spanish (Baus, Costa, & Carreiras, 2008; Pérez, 2007)—either returned inhibitory effects of PND on healthy college-aged Spanish-speaking adults (see also Vitevitch & Stamer, 2006) or null results.…”
Section: Discussioncontrasting
confidence: 47%
“…Consistent with this idea, we know of no study on healthy college-aged English-speaking adults that have found inhibitory effects for PND on speech onset latencies. All previous studies on this population have either found facilitatory effects (current study, Vitevitch, 2002; Vitevitch & Sommers, 2003) or null effects (Gordon & Kurczek, 2014; Munson, 2007; Newman & Bernsetin Ratner, 2007; Vitevitch, Armbrüster, & Chu, 2004). In contrast, the studies conducted by Sadat et al (2014)—including reanalyses of additional studies on Spanish (Baus, Costa, & Carreiras, 2008; Pérez, 2007)—either returned inhibitory effects of PND on healthy college-aged Spanish-speaking adults (see also Vitevitch & Stamer, 2006) or null results.…”
Section: Discussioncontrasting
confidence: 47%
“…For now and with the current data, we cannot unequivocally discard this possibility. One challenge to this account follows from the observation that in monolingual speech production phonological similarity among words has been shown to slow down lexical retrieval (e.g., Gordon & Kurczek, 2013; Sadat et al, 2014; see also Chan & Vitevitch, 2010, for slowing due to words with a rich neighborhood network; but see Vitevitch, 2002). Based on the assumption that such slowing is due to competitive processes and applying this logic to bilinguals, this would entail that phonologically highly similar translations should be detrimental to bilingual speech production.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidences have demonstrated that normal aging weakens not only top-down activation from semantics to phonology, but also bottom-up activation from phonology to semantics (Robert and Mathey, 2007;Robert and Duarte, 2016). Gordon and Kurczek (2014) reported that the effect of phonological neighborhood density on word production was facilitative in young adults but inhibitive in older adults, which suggests that there is an age-related decline in the activation transmission from shared phonemes to related lexical nodes (i.e., semantics). TOTs are usually accompanied with persistent alternatives (Burke et al, 1991;Heine et al, 1999;Kornell and Metcalfe, 2006), but the number of alternatives tends to be fewer for older adults because the bottom-up priming to the lexical nodes of alternates is decreased (Burke et al, 1991).…”
Section: The Current Studymentioning
confidence: 99%